Developing Guidelines for Age-Friendly Buses: a Survey of Older Peoples’ Preferences Regarding Headways, Distance to the Bus Stop and Destinations - Broome, Kieran; Worrall, Linda; Fleming, Jennifer; Boldy, Duncan (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
Background: Transport providers and policy makers should be guided by research evidence when developing age-friendly transportation services. There are significant gaps in the literature regarding older peoples’ preferences for bus headways, distance to the bus stop and destinations. Therefore, the aims of this study are to 1) quantify the preferred headways for older people, 2) quantify the preferred distance to the bus stop for older people, and 3) list and rank the preferred destinations of older people. Methods: A survey of community-dwelling older people in Hervey Bay and Brisbane (both in Australia) was conducted to quantify the preferences of older people regarding headways, distance to the bus stop and destinations. Results: One hundred participants completed the survey. The majority of older people preferred headways of a maximum of 30 minutes during the day and hourly at other times. The preferred distance to the bus stop was 200m or less. Preferred destinations included cross-suburban travel, leisure destinations, shops, central business district, medical services and other towns. Conclusion: These results contrast with usual practice and industry conventions. Transport providers and policy makers who are interested in providing age-friendly services should attempt to meet these guidelines. They may need to consider innovative approaches in order to meet these requirements.